PENGEMBANGAN PERPUSTAKAAN DIGITAL DI PROGRAM STUDI PENDIDIKAN TIK IKIP PGRI PONTIANAK - Ratih Widya Nurcahyo; Unung Verawardina; Ferry Marlianto (Jurnal Teknologi Informasi dan Pendidikan, 2019)
This research is entitled "Digital Library Development in Information Technology and Computer Education Study Program (P.TIK) IKIP PGRI Pontianak". The type of research used is research and development (R & D). The development model used is ADDIE. The subject of product trials for the implementation of digital libraries in this study were semester VI students. For small group trials conducted on a limited number of 15 students, consisting of students who have high, medium and low abilities, and field trials were conducted on 32 students. The data collection tool used in this study was a questionnaire. From the results of the study for the results of the feasibility validation of digital library products by media experts, the average score of 3.53 criteria was very good. Results from material experts obtained an average of 3.58 on the criteria very well. While the results of librarian experts obtained an average of 3.54 on the criteria very well. For the results of the digital library trials which were carried out limitedly on 15 students of the ICT Study Program IKIP-PGRI Pontianak obtained an average of 3.43 on the criteria very well. For the results of the best response obtained by 3.39 than the criteria good. Conclusions from the results of validation, trials and responses prove that digital libraries are feasible to use and can assist students in supporting lectures.